2016
DOI: 10.1212/wnl.0000000000002521
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bone resorption and increased bone mineral density in women with restless legs syndrome

Abstract: Despite lower 25-hydroxy vitamin D3, patients with RLS had lower bone resorption markers, higher lumbar BMD, and lower frequency of lumbar osteopenia. As patients with RLS make movements night and day to decrease the severity of their symptoms, they unconsciously perform exercise, which may potentially explain the better bone profile among patients with RLS than in controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Our study evaluated 1563 relevant literatures, but only 25 studies met the inclusion criteria, which contained a total of 3,603 subjects (Balaban et al., 2012; Bozkurt et al., 2012; Celik et al., 2015; Cikrikcioglu et al., 2016; Erden et al., 2014; Ghaderi et al., 2017; Gong et al., 2018; Gunduz et al., 2016; Han, Zhu, Shi, Wu, & Gu, 2017; Huang, Shah, Long, Crankshaw, & Tangpricha, 2013; Huzmeli, 2018; Kerley et al., 2016; Liguori et al., 2015; Majid et al., 2018; Mason et al., 2016; Mete et al., 2013; Neves et al., 2017; Pazarli, Ekiz, & Inonu Koseoglu, 2019; Qiao et al., 2018; Terzi & Yilmaz, 2016; Toujani et al., 2017; Uygur, Baki, Tanriverdi, Ornek, & Atalay, 2016; Wali et al., 2018; Zhao et al., 2017; Zicari et al., 2016). These 25 articles included 21 papers analyzing differences in vitamin D concentrations between sleep disorders and controls (Balaban et al., 2012; Bozkurt et al., 2012; Celik et al., 2015; Cikrikcioglu et al., 2016; Erden et al., 2014; Gong et al., 2018; Gunduz et al., 2016; Han et al., 2017; Huzmeli, 2018; Kerley et al., 2016; Liguori et al., 2015; Mete et al., 2013; Neves et al., 2017; Pazarli et al., 2019; Qiao et al., 2018; Terzi & Yilmaz, 2016; Toujani et al., 2017; Uygur et al., 2016; Wali et al., 2018; Zhao et al., 2017; Zicari et al., 2016) and 4 papers (RCTs) evaluating the change in the PSQI score in response to supplementation with vitamin D (Ghaderi et al., 2017; Huang et al., 2013; Majid et al., 2018; Mason et al., 2016). The detailed outcomes are presente...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study evaluated 1563 relevant literatures, but only 25 studies met the inclusion criteria, which contained a total of 3,603 subjects (Balaban et al., 2012; Bozkurt et al., 2012; Celik et al., 2015; Cikrikcioglu et al., 2016; Erden et al., 2014; Ghaderi et al., 2017; Gong et al., 2018; Gunduz et al., 2016; Han, Zhu, Shi, Wu, & Gu, 2017; Huang, Shah, Long, Crankshaw, & Tangpricha, 2013; Huzmeli, 2018; Kerley et al., 2016; Liguori et al., 2015; Majid et al., 2018; Mason et al., 2016; Mete et al., 2013; Neves et al., 2017; Pazarli, Ekiz, & Inonu Koseoglu, 2019; Qiao et al., 2018; Terzi & Yilmaz, 2016; Toujani et al., 2017; Uygur, Baki, Tanriverdi, Ornek, & Atalay, 2016; Wali et al., 2018; Zhao et al., 2017; Zicari et al., 2016). These 25 articles included 21 papers analyzing differences in vitamin D concentrations between sleep disorders and controls (Balaban et al., 2012; Bozkurt et al., 2012; Celik et al., 2015; Cikrikcioglu et al., 2016; Erden et al., 2014; Gong et al., 2018; Gunduz et al., 2016; Han et al., 2017; Huzmeli, 2018; Kerley et al., 2016; Liguori et al., 2015; Mete et al., 2013; Neves et al., 2017; Pazarli et al., 2019; Qiao et al., 2018; Terzi & Yilmaz, 2016; Toujani et al., 2017; Uygur et al., 2016; Wali et al., 2018; Zhao et al., 2017; Zicari et al., 2016) and 4 papers (RCTs) evaluating the change in the PSQI score in response to supplementation with vitamin D (Ghaderi et al., 2017; Huang et al., 2013; Majid et al., 2018; Mason et al., 2016). The detailed outcomes are presente...…”
Section: Resultsmentioning
confidence: 99%
“…The detailed outcomes are presented in Table 2, Table 3, Table S1, and Table S2. Celik et al, 2015;Cikrikcioglu et al, 2016;Erden et al, 2014;Gunduz et al, 2016;Huzmeli, 2018;Mete et al, 2013;Pazarli et al, 2019;Terzi & Yilmaz, 2016;Uygur et al, 2016), 3 studies were performed in Europe (Kerley et al, 2016;Liguori et al, 2015;Zicari et al, 2016), and 5 studies were performed in Asia (Gong et al, 2018;Han et al, 2017;Qiao et al, 2018;Wali et al, 2018;Zhao et al, 2017) (the America group and Africa group were not analyzed because only 1 paper was included, respectively (Neves et al, 2017;Toujani et al, 2017)). Seven studies used EI to analyze the vitamin D levels (Balaban et al, 2012;Celik et al, 2015;Cikrikcioglu et al, 2016;Gong et al, 2018;Mete et al, 2013;Qiao et al, 2018;Zhao et al, 2017), and 6 studies used CI (Erden et al, 2014;Kerley et al, 2016;Neves et al, 2017;Pazarli et al, 2019;Uygur et al, 2016;Zicari et al, 2016),…”
Section: Re Sultsmentioning
confidence: 99%
“…These studies suggest a negative feedback loop may be occurring between reduced sleep and poor bone health (Silverman, 1992;Foley et al, 2004). Interestingly, Cikrikcioglu et al found that women with restless legs syndrome had increased lumbar BMD, despite lower vitamin D levels, possibly due to unconsciously performing exercise (Cikrikcioglu et al, 2016).…”
Section: Sleep Disordersmentioning
confidence: 99%
“…1 In the article "Reduced bone resorption and increased bone mineral density in women with restless legs syndrome," the authors asked whether women with restless legs syndrome had changes in bone heath compared to women of similar ages and weights. 2 …”
Section: Do Women With Restless Legs Syndrome Have Less Bone Loss?mentioning
confidence: 99%